2021
DOI: 10.1021/acsami.1c09463
|View full text |Cite
|
Sign up to set email alerts
|

MOF-Embedded Bifunctional Composite Nanofiber Membranes with a Tunable Hierarchical Structure for High-Efficiency PM0.3 Purification and Oil/Water Separation

Abstract: Herein, a unique hierarchically structured composite nanofiber membrane, consisting of a zeolitic imidazolate framework-8-embedded polyethersulfone (PES@ZIF8) fiber layer and a polysulfonamide/polyethersulfone (PSA/PES) fiber layer, was successfully developed to cope with the complex environments during the actual filtration/separation process and overcome the conflict between high filtration efficiency and low air pressure resistance. Due to the advantages of the synergistic effect of multicomponents and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…In comparison, the nanofiber membrane fabricated by electrospinning technology has superior characteristics of thin diameter, large specific surface area, interconnected pore structure, and high porosity, which are conducive to high interception and capture of tiny aerosol particles [10][11][12]. Under unremitting researches, a large amount of high molecular polymer materials, such as PVDF, PSA, PAN, and PMIA, have been successfully fabricated by the electrospinning method [13][14][15][16]. Ding et al reported an integrated microfiber, nanofiber and nanonets filter by a combination of three layers with different fiber diameters in sequence [17].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the nanofiber membrane fabricated by electrospinning technology has superior characteristics of thin diameter, large specific surface area, interconnected pore structure, and high porosity, which are conducive to high interception and capture of tiny aerosol particles [10][11][12]. Under unremitting researches, a large amount of high molecular polymer materials, such as PVDF, PSA, PAN, and PMIA, have been successfully fabricated by the electrospinning method [13][14][15][16]. Ding et al reported an integrated microfiber, nanofiber and nanonets filter by a combination of three layers with different fiber diameters in sequence [17].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, scholars have made significant efforts and found that compared with the traditional oil–water separation materials, the superwetting separation materials demonstrate high purity, environmental protection, low cost, and simple operation for emulsion separation 11–13 . Considering these advantages, researchers have successfully formulated a few two‐dimensional (2D) superwetting separation materials, including metal‐mesh, fiber membranes, biological fabrics, and polymeric membranes, which can perform decent emulsion separation 14–17 . The accepted separation mechanism using these superwetting materials is a simple screening filtration mechanism, 18 wherein the oil and water phases have different surface tension on the pore of the separation material.…”
Section: Introductionmentioning
confidence: 99%
“…Considering these advantages, researchers have successfully formulated a few two-dimensional (2D) superwetting separation materials, including metal-mesh, fiber membranes, biological fabrics, and polymeric membranes, which can perform decent emulsion separation. [14][15][16][17] The accepted separation mechanism using these superwetting materials is a simple screening filtration mechanism, 18 wherein the oil and water phases have different surface tension on the pore of the separation material. Hence, the pore size of the separation material must be lower than the droplet size.…”
mentioning
confidence: 99%
“…Among the available air filter materials, fiber-based air filters have proven to be the most potentially effective treatment due to their high porosity, high surface area, lightweight, etc. Electrospinning was introduced to effectively resolve the PM filtration problem, which is used to produce advanced nanofiber filter media with small-diameter nanofibers, a high surface area, extensively interconnected pores, and a steerable morphology, and it also allows the large scalability of fabrication methods using different source materials. , Therefore, electrospinning is extensively used to prepare various nanofiber air filter media in comparison to other methods such as glass fibers and spun-bond fibers. Research is underway all over the world to enhance the filtration property of various individual polymers, such as PAN, polyethersulfone (PES), polyamide (PA), polyimide (PI), PVP, polyethylene terephthalate (PETE), and Nylon 6,6 . Due to the lack of functional groups, the PM removal efficiency of these filter media is limited.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Therefore, electrospinning is extensively used to prepare various nanofiber air filter media in comparison to other methods such as glass fibers and spunbond fibers. Research is underway all over the world to enhance the filtration property of various individual polymers, such as PAN, 13 polyethersulfone (PES), 14 polyamide (PA), 15 polyimide (PI), 16 PVP, 17 polyethylene terephthalate (PETE), 18 and Nylon 6,6. 19 Due to the lack of functional groups, the PM removal efficiency of these filter media is limited.…”
Section: Introductionmentioning
confidence: 99%